Plaque of Our Lady of the Rosary Church - Mumbai Archive Project Team (Jio Institute, 2024)
Following a schism in the church administration, the British government allowed Christian Kolis to build a church for their community a few metres away from the old Gloria Church, where the natives were denied entry in 1794. This church, consecrated as Our Lady of the Rosary, was built in the same year, with the date inscribed on its outer wall.